Borderline ovarian tumors: clinical characteristics, management, and outcomes - a multicenter study. Issue 1 (December 2016) - Gokcu, Mehmet; Gungorduk, Kemal; Aşıcıoğlu, Osman; Çetinkaya, Nilüfer; Güngör, Tayfun; Pakay, Gonca; Cüylan, Zeliha; Toptaş, Tayfun; Özyurt, Ramazan; Ağaçayak, Elif; Ozdemir, Aykut; Erol, Onur; et al.
Abstract Background The optimal surgical management and staging of borderline ovarian tumors (BOTs) are controversial. Institutions have different surgical approaches for the treatment of BOTs. Here, we performed a retrospective review of clinical characteristics, surgical management and surgical outcomes, and sought to identify variables affecting disease-free survival (DFS) and overall survival (OS) in patients with BOTs. Methods A retrospective review of ten gynecological oncology department databases in Turkey was conducted to identify patients diagnosed with BOTs. The effects of type of surgery, age, stage, surgical staging, complete versus incomplete staging, and adjuvant chemotherapy were examined on DFS and OS. Results In total, 733 patients with BOTs were included in the analysis. Most of the staged cases were in stage IA (70.4 %). In total, 345 patients underwent conservative surgeries. Recurrence rates were similar between the conservative and radical surgery groups (10.5 % vs. 8.7 %). Furthermore we did not find any difference between DFS (HR = 0.96; 95 % confidence interval, CI = 0.7–1.2;p = 0.576) or OS (HR = 0.9; 95 % CI = 0.8–1.1;p = 0.328) between patients who underwent conservative versus radical surgeries. There was also no difference in DFS (HR = 0.74; 95 % CI = 0.8–1.1;p = 0.080) or OS (HR = 0.8; 95 % CI = 0.7–1.0;p = 0.091) between complete, incomplete, and unstaged patients. Furthermore, receiving adjuvant chemotherapy (CT) for tumor stage ≥ IC was not an independent prognostic factor for DFS or OS. Conclusions Patients undergoing conservative surgery did not show higher recurrence rates; furthermore, survival time was not shortened. Detailed surgical staging, including lymph node sampling or dissection, appendectomy, and hysterectomy, were not beneficial in the surgical management oF BOTs.